The riparian reactive interface: a climate-sensitive gatekeeper of global nutrient cycles - Stutter, Marc; Baggaley, Nikki J.; Davies, Jess; Gagkas, Zisis; Janes-Bassett, Victoria; Laudon, Hjalmar; Lilly, Allan; Lupon, Anna; Musolff, Andreas; Trojahn, Sara; Haygarth, Philip M. (Frontiers in Environmental Science, 2023)
Riparian zones are critical interfaces to freshwater systems, acting as gateways for the conveyance and modification of macronutrient fluxes from land to rivers and oceans. In this paper we propose that certain riparian conditions and processes (conceptually ‘Riparian Reactive Interfaces’) may be susceptible to environmental change with consequences of accelerating local nutrient cycling cascading to global impacts on the cycles of carbon, nitrogen and phosphorus. However, we argue that this concept is insufficiently understood, and that research is unprepared to establish robust baseline data, predict and measure change in the key riparian ecosystem interface. We suggest one contributing factor as lack of interdisciplinary study of abiotic and biotic processes linking C, N and P dynamics. Another being emphasis on riparian ecology and restoration that limits frameworks for handling and scaling topography-soil-water-climate physical and biogeochemical observations from plot to large catchment scales. Scientific effort is required now to evaluate riparian current and future controls on global nutrient cycles through multi-nutrient (and controlling element) studies, grounded in landscape frameworks for dynamic riparian behaviour variation, facilitating scaling to catchment predictions.